2015
DOI: 10.1038/jhh.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Walking speed and high blood pressure mortality risk in a Spanish elderly population

Abstract: This study analyzed the relationship between blood pressure and all-cause mortality according to objectively measured walking speed in a Mediterranean population-based sample of older persons. We used data from the longitudinal 'Peñagrande' Cohort Study, initiated in 2008 in a sex- and age-stratified random sample of 1250 people aged ⩾65 years living in Madrid (Spain). A total of 814 individuals participated in the first study wave. The average of two standardized blood pressure readings was used. Walking spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
(45 reference statements)
1
15
0
2
Order By: Relevance
“…Our findings are consistent with prior studies showing that the association of high BP with CV events and mortality was attenuated or inverted in elders with poor functional status . We extended previous research by examining the role of grip strength, an indicator of overall body strength and physical function, in the association of BP with death.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with prior studies showing that the association of high BP with CV events and mortality was attenuated or inverted in elders with poor functional status . We extended previous research by examining the role of grip strength, an indicator of overall body strength and physical function, in the association of BP with death.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with prior studies showing that the association of high BP with CV events and mortality was attenuated or inverted in elders with poor functional status. 26,27,[33][34][35][36]38 We extended previous research by examining the role of grip strength, an indicator of overall body strength and physical function, 28 in the association of BP with death. Our findings suggest, compared to gait speed, grip strength may be a better marker of functional status in identifying subgroups of older adults in whom low BP is potentially beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty status is probably the most important factor modifying the relationship between blood pressure and outcomes of both observational studies among the community and institutionalized geriatric populations [8][9][10][21][22][23]. Longitudinal analysis of primary care electronic health record data for a large cohort of community-dwelling octogenarians in the United Kingdom found that mortality rates increased with frailty category [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on physical strength factors have demonstrated that the incidence of diabetes is highly related to reduced skeletal muscle mass 42 and that elderly individuals with diabetes have weak grip strength 43, 44 . In addition, there is an association between elderly individuals with hypertension and slow gait speed 45,46 . In Korea, elderly individuals with hypertension and diabetes have been shown to have weak grip strength 9,47 .…”
Section: Introductionmentioning
confidence: 99%